STRATEGI PENGEMBANGAN INDUSTRI KREATIF BANDUNG OLEH PEMERINTAH KOTA BANDUNG DALAM MENGANTISIPASI IMPLEMENTASI ASEAN FREE TRADE AREA DAN ASEAN ECONOMIC COMMUNITY - Mariane Delanova (Dinamika Global : Jurnal Ilmu Hubungan Internasional, 2019)
ASEAN Free Trade Area (AFTA) and ASEAN Economic Community (AEC) has been implemented since 2015. It means ASEAN make a step into a new era, called free trade era, which is reducing all trade barriers, include tariff and non tarrif barriers. ASEAN has a vision, by implementing AFTA and EAC, to make Southeast Asia region can improve its economic sector, also improving economic sector of its member states, and so Indonesia. This research focuses on the strategic of Pemerintah Kota Bandung (The Local Government of Bandung City) to develop and improve the creative industres of Bandung City, especially in the era of AFTA and AEC. Also this research will explore the obstacles of creative industries of Bandung City in the era of AFTA and AEC. Creative industres of Bandung City have to reach the benefit from the implementing of AFTA and AEC, so creative industries of Bandung City will contribute to Indonesia’s national income, especially increasing Bandung City’s income.